Neonatal health care costs of very preterm babies in England: a retrospective analysis of a national birth cohort - Neena Modi; Helen Campbell; Miaoqing Yang; Oliver Rivero-Arias; Thillagavathie Pillay; Elaine M Boyle (BMJ Publishing Group, 2023)
Objectives Babies born between 27+0 and 31+6 weeks of gestation represent the largest group of very preterm babies requiring National Health Service (NHS) care; however, up-to-date, cost figures for the UK are not currently available. This study estimates neonatal costs to hospital discharge for this group of very preterm babies in England.Design Retrospective analysis of resource use data recorded within the National Neonatal Research Database.Setting Neonatal units in England.Patients Babies born between 27+0 and 31+6 weeks of gestation in England and discharged from a neonatal unit between 2014 and 2018.Main outcome measures Days receiving different levels of neonatal care were costed, along with other specialised clinical activities. Mean resource use and costs per baby are presented by gestational age at birth, along with total costs for the cohort.Results Based on data for 28 154 very preterm babies, the annual total costs of neonatal care were estimated to be £262 million, with 96% of costs attributable to routine daily care provided by units. The mean (SD) total cost per baby of this routine care varied by gestational age at birth; £75 594 (£34 874) at 27 weeks as compared with £27 401 (£14 947) at 31 weeks.Conclusions Neonatal healthcare costs for very preterm babies vary substantially by gestational age at birth. The findings presented here are a useful resource to stakeholders including NHS managers, clinicians, researchers and policymakers.